Impact of Pretreatment and Drying Factors on Chemical and Biochemical Attributes of Moroccan Thompson Seedless Grapes - Abdelhakim Boudboud; Mohamed Ben Aziz; Hassan Hajjaj; Lhoussain Hajji; Bruno de Meulenaer; Hamid Mazouz (International Journal of Food Science)
Drying is a common technique in the agrifood industry, but insufficient control in the drying process can result in changes to the fruit’s appearance due to physiological damage during processing. The aim of this study was to investigate the impact of pretreatment and drying process parameters on Moroccan raisins’ quality and safety. The experimental levels of pretreatment factors (blanching, browning agents) and drying temperature were defined at the beginning. Subsequently, a 24-factorial design was employed to provide a simple and reliable model capable of relating directly the response factor (drying time, color intensity change (E∗), chromaticity (C∗), and browning rate) to the variables (NaOH concentration, antibrowning agent concentration, temperature, and relative humidity). All four parameters had a statistically considerable effect on studied responses. Blanching for 5 minutes at 1% of NaOH solution, using an appropriate concentration of antibrowning agent (5% Na2S2O5), and drying at 70°C with 30% of relative moisture can lead to better preservation of grapes’ appearance and quality (chromaticity (C∗) and color change (E∗)). Also, in these conditions, a lower browning rate (14.48%), a lower 5-hydroxymethylfurfural content (12.40 mg/100 g DW), and a higher level of polyphenols (135.79±13.17 mg GAE/100 g DW) and flavonoid content (57.81±3.08 mg Qeq/100 g DW) have been recorded while meeting international standards for SO2 content and microbial quality.